Gesture imitation and recognition using Kinect sensor and extreme learning machines - Yavşan, Emrehan; Uçar, Ayşegül (My University, 2016)
This study presents a framework that recognizes and imitates human upper-body motions in real time. The framework consists of two parts. In the first part, a transformation algorithm is applied to 3D human motion data captured by a Kinect. The data are then converted into the robot’s joint angles by the algorithm. The human upper-body motions are successfully imitated by the NAO humanoid robot in real time. In the second part, the human action recognition algorithm is implemented for upper-body gestures. A human action dataset is also created for the upper-body movements. Each action is performed 10 times by twenty-four users. The collected joint angles are divided into six action classes. Extreme Learning Machines (ELMs) are used to classify the human actions. Additionally, the Feed-Forward Neural Networks (FNNs) and K-Nearest Neighbor (K-NN) classifiers are used for comparison. According to the comparative results, ELMs produce a good human action recognition performance.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Human action recognition; NAO humanoid robot; Xbox 360 Kinect; Extreme learning machines